Estudo prospectivo sobre a utilização de próteses totais implantossuportadas em pacientes edêntulos - Compagnoni, Marco Antonio [UNESP]; Paleari, André Gustavo [UNESP]; Rodriguez, Larissa Santana [UNESP]; Marin, Danny Omar Mendoza [UNESP]; Oliveira Júnior, Norberto Martins de [UNESP]; Pero, Ana Carolina [UNESP] (My University, 2012)
The objective of this study was to evaluate the impact of replacing conventional mandibular complete dentures by complete fixed dentures on the oral health-related quality of life and kinesiographic parameters of maxillary edentulous patients. Material and Methods: edentulous patients (n = 16) received one set of new complete dentures and after the intraoral adjustments and adaptation period (30 days), the Brazilian version of Oral Health Impact Profile for assessing edentulous subjects (Ohip-Edent) was used to evaluate the oral health-related quality of life (OHQOL) of the participants. Additionally, the kinesiograph instrument K6-I (Myotronics Research Inc., Seattle, WA) was used to record opening and closure range of movement, mandibular movement, and the pattern of maxillary complete denture movement on chewing. Afterwards, the patients had their mandibular complete dentures replaced by a complete fixed denture and the same evaluation protocol was performed after 3 and 6 months. Ohip-Edent responses were analyzed using Wilcoxon's test for repeated measures (α = .05) and Kinesiographic data using the Student´s t test (α = .05). Results: The Ohip-Edent showed an improvement of general oral health-related quality of life after 3 and 6 months of the treatment with complete fixed dentures. Kinesiographic recordings revealed a significant increase on maximum mandibular movements of vertical opening and no differences for the movement of the maxillary complete denture on chewing after treatment with complete fixed dentures was observed. Conclusion: the installation of complete fixed dentures improved the OHQOL and changed mandibular movements, with increases in vertical amplitude of maximal opening.

O objetivo deste estudo foi avaliar o impacto da substituição de próteses totais convencionais mandibulares por próteses totais implantossuportadas sobre a qualidade de vida e os parâmetros cinesiográficos em pacientes desdentados totais bimaxilares. Métodos: indivíduos desdentados totais bimaxilares (n = 16) receberam próteses totais novas e após um período de adaptação (30 dias), a versão brasileira do Oral Health Impact Profile para indivíduos desdentados (Ohip-Edent) foi usada para avaliar a qualidade de vida relacionada à saúde oral dos participantes. Além disso, o cinesiógrafo K6-I (Myotronics Research Inc., Seattle, WA) foi utilizado pra realizar os registros dos movimentos máximos de abertura e fechamento e movimentação da prótese total superior durante a mastigação. Posteriormente, os indivíduos tiveram suas próteses totais convencionais mandibulares substituídas por próteses totais implantossuportadas e o mesmo protocolo de avaliação foi realizado após três e seis meses. Os resultados do Ohip foram avaliados utilizando os testes de Wilcoxon (α = 0,05) e os dados cinesiográficos avaliados por meio do teste t Student (α = 0,05). Resultados: os participantes apresentaram uma melhora significativa na qualidade de vida relacionada à saúde oral após três e seis meses de tratamento com próteses totais implantossuportadas. Os registros cinesiográficos demonstraram aumento significativo no movimento de abertura máxima vertical e nenhuma diferença significante foi encontrada no movimento da prótese total superior durante a mastigação após o tratamento com próteses totais implantossuportadas. Conclusão: a instalação de próteses totais implantossuportadas melhora a qualidade de vida dos pacientes e promove aumento na amplitude da abertura mandibular vertical.
Prospective study of the use of complete fixed dentures in edentulous patients
Keywords: Mandible; Mouth edentulous; Dental implantation; Denture complete; Mandíbula; Boca edentada; Implante dentário; Prótese total